Perioperative change in CA125 is an independent prognostic factor for improved clinical outcome in advanced ovarian cancer. (September 2019) - Timmermans, M.; Zwakman, N.; Sonke, G.S.; Van de Vijver, K.K.; Duk, M.J.; van der Aa, M.A.; Kruitwagen, R.F.
Abstract: Objective: Despite being the most important prognostic factor for prolonged overall survival in epithelial ovarian cancer (EOC), the measurement of residual disease is hampered by its subjective character. Additional assessment tools are needed to establish the success of cytoreductive surgery in order to predict patients' prognosis more accurately. The aim of this study is to evaluate the independent prognostic value of perioperative CA125 change in advanced stage EOC patients. Study design: We identified all patients who underwent primary cytoreductive surgery for advanced stage (FIGO IIB-IV) EOC between 2008 and 2015, from the Netherlands Cancer Registry. The relative perioperative change in CA125 was categorized into four groups; increase, <50% decline, 50–79% decline and ≥80% decline. Overall survival (OS) was analyzed using Kaplan-Meier survival curves and multivariable cox regression models. Results: We included 1232 eligible patients with known pre- and postoperative CA125 serum levels. Patients with a decline of ≥80% in CA125 levels experienced improved OS compared to those with a decline of <50% (univariable Hazard Ratio (HR) 0.45, 95%CI 0.36-0.57). The prognostic effect of perioperative CA125 change was independent of patient- and treatment characteristics, such as the extent of residual disease after cytoreductive surgery (multivariable HR≥80% 0.52(0.41-0.66)). Conclusions: This study shows that the perioperative change in CA125 is an independent prognostic factor for overall survival after primary surgery for EOC patients. This pleads for the use of a combined model, consisting of perioperative CA125 change and the outcome of residual disease, in order to predict the prognosis of EOC patients more accurately.